Intimate partner violence: short and long term consequences - Corazziari, Isabella; Muratore, Maria Giuseppina (La camera blu. Rivista di studi di genere, 2015)
The work analyses the short and long-term consequences of intimate partner violence and the strategies that women have developed to get out of violence. A causal model is developed to analyse five different multivariate dimensions characterising intimate partner violence, based on the last and unique national representative population survey about violence against women. In a second step the stories of repeated violence will be analysed focusing on the strategies the victims have used to cope with violence. The most effective strategies will be contrasted with the less ones. Less effective strategies are associated with an increasing risk of the cycle of violence, that is those who have suffered violence as a child are likely to accept it enduring in their adult life. The analysis of the physical, moral and psychological consequences, shows a mixed picture, linked to both the severity of the violence, and to the type of suffered violence; focusing on the history of violence, the various strategies to cope with it are closely linked to the framework of severity, to the characteristics and dynamics of the violence and to the specific history that each woman lives.